Relationships between role stress, professional identity, and burnout among contemporary school counselors. Issue 8 (6th April 2021) - Maor, Rotem; Hemi, Alla
Abstract: Continuous exposure to stress has psychological and physiological consequences for employees, especially for mental health professionals whose professions are known as demanding and stressful. The current study focuses on the relationship between role stress and burnout in the contemporary school counselors' role. We also aimed to examine whether professional identity might serve as a protective mechanism against burnout. School counselors ( N = 205, 96% female, mean age = 43.03) currently practicing in the Israeli education system filled out questionnaires assessing their perceived role stress, burnout, and professional identity. Results indicated that school counselors perceived noncounseling role stressors as more stressful than counseling role stressors. Noncounseling role stressors contributed to burnout more than counseling role stressors. Professional identity was negatively correlated with burnout. Last, professional identity moderated the relationship between role stress and burnout. Findings highlight the negative impact of noncounseling stressors on burnout and the importance of professional identity as a protective factor against burnout among school counselors.